Marine biorefinery: valorisation of algae into advanced products - Martins, Ana Margarida Ferreira (2021)
The consumption paradigm is changing. Consumers are more attentive to what they consume and to the sustainability questions addressed to those products. This change was driven by the healthy label given to natural products but also by the urgent need to find more sustainable sources of raw materials and to implement processes as a way to mitigate climate changes, without compromising the quality and affecting the price of the final product. Pigments are compounds that can be obtained from various sources of biomass, being recognized by their numerous biological activities. Due to their spectral and biological properties, pigments can find application in many fields, from food to cosmetics, nutraceutics, and medicine. However, conventional methodologies to obtain pigments demand very often the use of costly equipment and/or toxic organic solvents. In this work, alternative methodologies to extract and purify pigments from algae of were developed. Simple and efficient methodologies mostly based on aqueous solvents were used to recover one or more pigments from algae within a blue biorefinery framework. In all chapters, a variety of solvents were screened, and operational conditions were studied and optimized in order to reach high yields of extractions and/or purities. Aqueous solutions of tensioactive ionic liquids have shown great potential for the recovery of hydrophobic pigments such as chlorophylls and carotenoids. In the other hand, induced precipitation of proteins is shown to be a good alternative for the selective precipitation (and further purification) of phycobiliproteins. Economic and environmental impacts were assessed and encouraging results were obtained from both perspectives, leading us to believe in the potential for the industrial implementation of some of the results here obtained.